Beaming of inductive field with an asymmetric four-coil resonator for wireless power transfer - Wan Fauzi, Wan Noor Nadira; Mazli, Mohamad Syafiq; Khan, Sheroz; Adnan, Khairil Azhar; Aboadla, Ezzidin Hassan Elmabrouk; Tohtayong, Majdee; Yaacob, Mashkuri (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
This paper suggests a high efficiency inductive wireless power transfer system can be achieved by improving beaming field. Theoretical analysis, simulation results and experimental results are presented in this report. The coupling coefficient is enhanced through the use of multi-coils on the primary, ensuring a long distance transfer over a wide operating frequency range. It is a significant technique to overcome the shortcomings of wired charging. A prototype is constructed and the optimum air gap between the primary side and the secondary side for the power transmission is 15mm with 60 kHz of switching frequency. The results obtained reveals that asymmetric 4-coil resonator has greater power transfer efficiency for a similar gap compared to symmetric 4-coil resonator as the source coil effective inductance is boosted two times by intermediate coils at the primary side.